Bioaccumulation of Heavy Metals (Arsenic, Cadmium and Lead) in the Fish Lates niloticus from Alaro hydroecosystem, Ibadan (2015)
A study was carried out on the bioaccumulation of heavy metals (Arsenic, Cadmium and Lead) in the fish Lates niloticus from Alaro hydroecosystem, Ibadan. Fish were sampled and collected between January and December 2003 which was representative of dry and rainy season. Liver, muscle, gills, bones, gut and fins were acid-digested and analyzed for arsenic (As), cadmium (Cd) and lead (Pb) using the inductively coupled plasma-mass spectrometer (ICP-MS).Quality assurance of the results was assured through the use of bovine liver from the National Institute of Standards and Technology (NIST) as Standard Reference Material (SRM). The range of heavy metals As, Cd and Pb in the fish organs were 0.000-0.201ppm, 0.000-0.342ppm and 0.00-14.12ppm respectively. The mean concentration of As in all the fish organs exceeded World Health Organization (WHO) guideline while that of Cd concentration in the fin (0.049ppm) was below the WHO guideline and all the other organs exceeded it. For Pb, all the organs exceeded the WHO recommended guideline limit of 1ppm. Hence, this study shows that Alaro stream is impacted by grossly polluted effluents rich in heavy metals and therefore fish (L.niloticus) caught from it is unfit for human consumption due to public health threats associated with their toxicity